Analisis Faktor Pengetahuan, Sikap dan Perilaku Keluarga dalam Deteksi Dini Hipertensi Emergency di Tingkat Prehospital - Dila Nur Isnaeni Rahmah; Shinta Arini Ayu; Sri Kurnia Dewi (Jurnal Sehat Mandiri, 2025)
Emergency hypertension is a critical condition of high blood pressure accompanied by target organ damage, and requires immediate treatment to prevent serious complications. In the prehospital setting, early detection by the family is very important to prevent further harm. Factors such as family knowledge, attitudes, and behavior are considered to play a role in the early detection process. This study aims to determine the relationship between knowledge, attitudes, and family behavior towards early detection of emergency hypertension in the prehospital environment in Desa Sindanglaka. This study used a quantitative approach with a cross-sectional design. The sample amounted to 53 respondents who were families of people with hypertension. Data were collected using questionnaires and observation sheets, then were analyzed using the Chi-Square test. The results showed that there was no significant relationship between knowledge (p = 0.052), attitude (p = 0.919), and behavior (p = 0.788) of the family towards early detection of emergency hypertension. There is no significant relationship between family knowledge, attitudes, and behavior with early detection of emergency hypertension in the prehospital setting. Education and increased family participation in early detection efforts are needed to reduce the number of complications due to emergency hypertension.